Aplikasi Edible Coating Lidah Buaya (Aloe vera L.) terhadap Mutu Terung (Solanum melongena L.) - Iqlima Emil Hartass; Tuti Heiriyani; Rabiatul Wahdah (Universitas Lambung Mangkurat, 2020)
Eggplant contain high fiber, so it’s good for digestion. But sometimes utilization in fresh condition has limitations because eggplant is easily loss a quality. Therefore, the application of edible coatings is expected to protect the surface of the fruit. The application of natural edible coatings can be given, one of which is the basic ingredients of aloe vera.. Aloe vera can maintain the moisture of the fruit cell wall and is permeable to transfer gas and water and prevent chilling injuries. Application of a coating with polysaccharides can usually increase the thickness of the coating. Completely Randomized Design one factor was used with different concentration: G1= aloe vera gel 100% + glycerol 1% + pectin 1%; G2= aloe vera gel 50% + glycerol 1% + pectin 1%; G3= aloe vera gel 100% + glycerol 1,5% + pectin 1,5%; G4= aloe vera gel 50% + glycerol 1,5% + pectin 1,5%.The results showed that the application of Aloe vera's edible coating effect in reducing eggplant weight loss is equal to 13.16%. However, this application is not effective to maintain the quality of the eggplant. It would be better if the eggplant is stored at a low temperature. In addition to extending the shelf life of eggplant can be used as other food processed products